2005
DOI: 10.1191/0960327105ht509oa
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of Withania somnifera on 6-hydroxydopamine induced Parkinsonism in rats

Abstract: 6-Hydroxydopamine (6-OHDA) is one of the most widely used rat models for Parkinson's disease. There is ample evidence in the literature that 6-OHDA elicits its toxic manifestations through oxidant stress. In the present study, we evaluated the anti-parkinsonian effects of Withania somnifera extract, which has been reported to have potent anti-oxidant, anti-peroxidative and free radical quenching properties in various diseased conditions. Rats were pretreated with 100, 200 and 300 mg/kg b.w. of the W. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(112 citation statements)
references
References 36 publications
(11 reference statements)
3
96
0
Order By: Relevance
“…Root extracts from this species have also been shown to significantly reduce the number of hippocampal degenerating cells in the brains of stressed rodents (Jain et al, 2001) and were neuroprotective in animal models of Parkinson's disease (Ahmad et al, 2005;Sankar et al, 2007) and Huntington disease (Kumar and Kumar, 2009) . Although some in vivo studies using various animal models suggest W. somnifera extracts can improve antioxidant status and provide neuroprotection (Jain et al, 2001;Parihar and Hemnani, 2003;Sankar et al, 2007;Bhatnagar et al, 2009) Invitrogen (UK).…”
Section: Introductionmentioning
confidence: 99%
“…Root extracts from this species have also been shown to significantly reduce the number of hippocampal degenerating cells in the brains of stressed rodents (Jain et al, 2001) and were neuroprotective in animal models of Parkinson's disease (Ahmad et al, 2005;Sankar et al, 2007) and Huntington disease (Kumar and Kumar, 2009) . Although some in vivo studies using various animal models suggest W. somnifera extracts can improve antioxidant status and provide neuroprotection (Jain et al, 2001;Parihar and Hemnani, 2003;Sankar et al, 2007;Bhatnagar et al, 2009) Invitrogen (UK).…”
Section: Introductionmentioning
confidence: 99%
“…A polyherbal preparation, BR-16 (Mentat®), which includes WS as one of the major component exhibited significant protective effect against reserpine-induced catalepsy in mice (Kumar and Kulkarni 2006). Few studies have demonstrated the protective efficacy of WS root extracts, against oxidative stress and degeneration of hippocampal cells in vivo under stress conditions (Parihar and Hemnani 2003;Sankar et al 2007;Ahmad et al 2005;Kumar and Kumar 2009). However, not many studies have demonstrated the neuroprotective efficacy of WS in Parkinson's disease (PD) models (Manjunath and Muralidhara 2013).…”
mentioning
confidence: 99%
“…medicinal properties, such as immunomodulatory, [17] antiinflammatory, [18] endocrine, [19] anti-stress, [20] anti-cancer, [21 adaptogenic, [22] anti-tumor, [23] central nervous system, [24,25] cardiovascular, [26,27] and neuroprotective [28] activities, respectively. Among the other parts of this plant, the root has been considered to be the most active part for therapeutic purposes.…”
mentioning
confidence: 99%